2018
DOI: 10.4269/ajtmh.17-0912
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Taenia solium Oncosphere Infection: A Novel Porcine Neurocysticercosis Model

Abstract: Neurocysticercosis (NCC), the infection of the human central nervous system (CNS) with larval cysts of causes widespread neurological morbidity. Animal models are crucial for studying the pathophysiology and treatment of NCC. Some drawbacks of current NCC models include differences in the pathogenesis of the model and wild-type parasite, low rates of infection efficiency and lack of reproducibility. We describe a novel porcine model that recreates infection in the CNS with high efficiency. Activated oncosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…The review process and the number of articles selected at each stage of the review is shown in Fig 1 . From an initial number of 166 articles, only 8 studies that performed experimental infections were included in this review (including the unpublished study): 2 studies using the “Proglottid” pathway [ 30 , 31 ], 4 studies using the “Eggs” pathway [ 30 , 32 , 36 ], 3 studies using the “Beetles” pathway [ 33 , 34 ], and 2 studies using the “Carotid” pathway [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The review process and the number of articles selected at each stage of the review is shown in Fig 1 . From an initial number of 166 articles, only 8 studies that performed experimental infections were included in this review (including the unpublished study): 2 studies using the “Proglottid” pathway [ 30 , 31 ], 4 studies using the “Eggs” pathway [ 30 , 32 , 36 ], 3 studies using the “Beetles” pathway [ 33 , 34 ], and 2 studies using the “Carotid” pathway [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the collection of T . solium eggs from the proglottids were performed by gentle homogenization [ 30 , 35 ], maceration [ 32 , 36 ] and direct mixing with cattle feces [ 33 , 34 ]. A more detailed description of the experimental designs is available in the publications referenced in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 The pathophysiologic mechanisms of NCC-induced hydrocephalus are not fully understood, although experimental models have helped solve some questions regarding leukocyte infiltration and inflammatory reactions-mainly for the parenchymal form of the disease. [14][15][16][17][18][19] Recently, we developed an experimental model of NCC-induced hydrocephalus that reproduces magnetic resonance imaging (MRI) and histologic findings of human NCC. 20 In the present study, we aimed to analyze the effects of albendazole treatment in a rat model of NCC with concomitant hydrocephalus to evalu-ate the correlation between the course of hydrocephalus and animal behavior.…”
Section: Introductionmentioning
confidence: 99%